Athlete doping confrontation efficacy and confrontation likelihood. (March 2023) - Harris, Tyler S.; Crowley, Mackenna M.; Heller, Hannah M.
Abstract: Evidence supports the role of coach doping confrontation efficacy (DCE; Sullivan et al., 2015) as a deterrent against athletes' doping cognitions (Boardley et al., 2019; Sullivan & Razavi, 2017), but the role of the athlete has largely been ignored. Current anti-doping campaigns encourage athletes to report doping misconduct (i.e., whistleblowing), but some athletes would prefer to confront the athlete directly (Erickson et al., 2017). Thus, it is important to consider what may contribute to athletes' likelihood to confront a doping teammate or opponent. The purpose of this study was to determine whether DCE could predict an athlete's likelihood to confront a doping teammate or opponent. Additionally, doping moral disengagement (MD) was included as a possible moderator of this relationship. Surveys were completed by 155 college athletes (nmale = 145) to measure their perceived DCE, doping MD, likelihood to confront a teammate, and likelihood to confront an opponent. Separate linear regression analyses were run for the two targets of confrontation. In the teammate model, both DCE and doping MD were significant predictors of confrontation likelihood. DCE was the only significant predictor in the opponent model. Neither model presented with a significant interaction, suggesting no moderation effect. Results suggest perceived DCE is associated with a greater likelihood to confront a doping athlete, regardless of whether they are a teammate or opponent; however, moral disengagement plays a greater role if the athlete is a teammate. These findings imply that confrontation may be the first line of defense against doping before whistleblowing action is taken. Research should continue to explore antecedents and consequences of athlete doping confrontation, providing greater insight into the whistleblowing process. Highlights: Athletes equally likely to confront a teammate as an opponent for doping. Confidence in ability to confront predicts likelihood to confront teammate/opponent. Moral disengagement may decrease likelihood of an athlete to confront a teammate only. Confrontation may be a possible first step in the whistleblowing process.